PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI PENJAJAHAN PADA PEMBELAJARAN IPS KELAS V SEKOLAH DASAR - Permatasari, Intan; Hakim, Lukman; Aryaningrum, Kiki (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This developmental research aims to develop colonial monopoly media in social studies learning material about the arrival of western nations at class V elementary school that is valid, practical and effective. Researchers used research methods, namely Research and Development (R&D), and used the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. Data collection techniques in this research are questionnaires, documentation and learning outcomes tests. The results of the validity research were obtained with an average score of media experts of 88% with very valid criteria, and an average score of material experts of 79% with very valid criteria, and an average score of linguists of 81% with very valid criteria. The results of product practicality research conducted using one to one student response questionnaires (4 students), Small Group (11 students) and teacher response questionnaires obtained average scores of 92%, 92% and 90%. Furthermore, with a product effectiveness test carried out by 15 class V students, they got an average score of 93% in the very effective category. It can be concluded that monopoly media on social studies learning for class V elementary school is very valid, practical and effective to be used and developed during teaching and learning activities in classroom activities for class V students at SD Negeri 96 Palembang.